2019
DOI: 10.1021/acs.inorgchem.9b01336
|View full text |Cite
|
Sign up to set email alerts
|

KCu7P3: A Two-Dimensional Noncentrosymmetric Metallic Pnictide

Abstract: Layered material, flux synthesis, p-type metal, aqueous stability ABSTRACT: We report a 2D material, KCu7P3 with a noncentrosymmetric structure (trigonal space group P31m, a = 6.9637(2) Å, c = 24.1338(10) Å), which forms both from a molten potassium polyphosphide flux and from the elements. This phase consists of infinite [Cu7P3]layers with hexagonal P sheets separated by K + ions. The structure of the layers is unique but related to both Cu3P and the CaCu4P2 structure-types. Single-crystal refinement reveals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…“Can a metal be polar like ferroelectrics?” Starting from the theoretical considerations on this insightful question by Anderson and Blount, [ 324 ] polar metals (ferroelectric‐like metals), in which two contradictory physical properties of acentric displacements and metallicity coexist, have attracted tremendous interest. [ 325–355 ] In particular, the polar metallic state is not common in a solid composed of a single element, because delocalized charge carriers (producing electrical conductivity in a metal) effectively screen out local electric dipoles resulting in ill‐defined macroscopic polarization. [ 330,353,356 ] Note that the conventional ferroelectric materials (e.g., Pb(Zr,Ti)O 3 and BaTiO 3 ), where switchable macroscopic polarization is well defined with a long‐range ordering of electric dipole moments, are electrically insulating with no delocalized d orbital electron (i.e., 3 d 0 ) due to the fully occupied electronic band structures.…”
Section: Emerging Functionalities By Polar Perturbationsmentioning
confidence: 99%
“…“Can a metal be polar like ferroelectrics?” Starting from the theoretical considerations on this insightful question by Anderson and Blount, [ 324 ] polar metals (ferroelectric‐like metals), in which two contradictory physical properties of acentric displacements and metallicity coexist, have attracted tremendous interest. [ 325–355 ] In particular, the polar metallic state is not common in a solid composed of a single element, because delocalized charge carriers (producing electrical conductivity in a metal) effectively screen out local electric dipoles resulting in ill‐defined macroscopic polarization. [ 330,353,356 ] Note that the conventional ferroelectric materials (e.g., Pb(Zr,Ti)O 3 and BaTiO 3 ), where switchable macroscopic polarization is well defined with a long‐range ordering of electric dipole moments, are electrically insulating with no delocalized d orbital electron (i.e., 3 d 0 ) due to the fully occupied electronic band structures.…”
Section: Emerging Functionalities By Polar Perturbationsmentioning
confidence: 99%
“…It was further accelerated by the discovery of nontrivial topological metals and their ensuing phenomena and properties [9][10][11]. During the rapid increase in scholarship, diverse methods of combining these previously contraindicated properties have been proposed and executed, ranging from degenerately doped ferroelectrics [12][13][14][15] to metals with hybrid improper polar distortions [16,17] to twodimensional thin films and interfaces [18][19][20]. Reviews of the classification of different design strategies for polar metals can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, complex copper chalcogenides are unusual in that they are often Cudeficient or mixed-valent, which often gives them p-type metallic conductivity. 20,21 For example, K 3 Cu 8 S 6 only contains (formally) monovalent Cu atoms and, accordingly, is missing one Cu atom per formula unit. 22 This gives the material a metallic p-type conductivity, where the charges (holes) are considered to be delocalized on the sulfur as well as the Cu sublattice, although there is some disagreement in the literature regarding the nature of the mixed-valency.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similar to the silver chalcogenides, ternary copper chalcogenides often crystallize in two-dimensional structures and have many of the same structural units. However, complex copper chalcogenides are unusual in that they are often Cu-deficient or mixed-valent, which often gives them p-type metallic conductivity. , For example, K 3 Cu 8 S 6 only contains (formally) monovalent Cu atoms and, accordingly, is missing one Cu atom per formula unit . This gives the material a metallic p-type conductivity, where the charges (holes) are considered to be delocalized on the sulfur as well as the Cu sublattice, although there is some disagreement in the literature regarding the nature of the mixed-valency. , Nevertheless, the delocalized nature of the charge carriers makes these systems type-III mixed-valent materials according to the Robin–Day classification …”
Section: Introductionmentioning
confidence: 99%